2019
DOI: 10.3126/njdvl.v17i1.23291
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Cushing Syndrome due to Application of Potent Topical Corticosteroid: A Case Report

Abstract: Corticosteroids are over the counter and cheaper drugs available in every medical stores in Nepal. Iatrogenic Cushing syndrome due to topical steroids application is a very rare phenomenon in adults.A 32 year female from Janakpur presented with complaints of swelling of face, weight gain, excessive facial hair and fatigue since two years that gradually increased over last one year. She had a past medical history of on and off application of multiple potent topical corticosteroids for disseminated Tinea infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
0
1
Order By: Relevance
“… 25 Bhusal M et al reported a 32-year-old female who developed iatrogenic Cushing's syndrome following the application of clobetasol propionate for disseminated tinea infection. 26 However in our study we did not find any systemic adverse effects.…”
Section: Discussioncontrasting
confidence: 59%
“… 25 Bhusal M et al reported a 32-year-old female who developed iatrogenic Cushing's syndrome following the application of clobetasol propionate for disseminated tinea infection. 26 However in our study we did not find any systemic adverse effects.…”
Section: Discussioncontrasting
confidence: 59%